2019
DOI: 10.1111/codi.14867
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of 8 weeks’ vs 12 weeks’ interval between neoadjuvant chemoradiotherapy and surgery for locally advanced rectal cancer

Abstract: Aim The aim was to compare the pathological complete response (pCR) rate at 8 compared to 12 weeks’ interval between completion of neoadjuvant chemoradiotherapy (CRT) and surgery in patients with locally advanced rectal cancer. Method This was a randomized trial which included a total of 330 patients from two institutions. Patients with locally advanced (T3‐4N0M0, TxN+M0) rectal cancer were randomized into 8‐ and 12‐week interval groups. All the patients received long‐course CRT (45 Gy in 1.8 Gy fractions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…When comparing 7 versus 11 weeks interval, there was no difference in complete response rates, tumour stage or TRG in a French study including 265 rectal cancer patients [31]. In two Turkish randomised trials [30,32] including a total number of 657 patients, comparing classic intervals (between 6 and 8 weeks) with prolonged intervals (10 weeks and 12 weeks respectively) there was an increase in pathological complete response and downstaging, but not in TRG.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…When comparing 7 versus 11 weeks interval, there was no difference in complete response rates, tumour stage or TRG in a French study including 265 rectal cancer patients [31]. In two Turkish randomised trials [30,32] including a total number of 657 patients, comparing classic intervals (between 6 and 8 weeks) with prolonged intervals (10 weeks and 12 weeks respectively) there was an increase in pathological complete response and downstaging, but not in TRG.…”
Section: Introductionmentioning
confidence: 94%
“…Unfortunately, there is a huge variation in timing within and between different studies, which makes comparisons very difficult. Moreover, results from randomised clinical trials focussing on this interval are conflicting [30][31][32]. When comparing 7 versus 11 weeks interval, there was no difference in complete response rates, tumour stage or TRG in a French study including 265 rectal cancer patients [31].…”
Section: Introductionmentioning
confidence: 99%
“…Two randomized trials by Akgun et al [32] and Terzi et al [33] have demonstrated that pCR rates are higher for long intervals (> 8 weeks) than for short intervals, although both intervals have exhibited similar rates in postoperative mortality and morbidity. However, the GRECCAR-6 trial revealed no significant difference between long (11 week) and short intervals (7 weeks) with respect to pCR occurrence, although greater complications and difficulties in surgery were observed for participants with an 11-week interval [34].…”
Section: Discussionmentioning
confidence: 99%
“…This approach (scRT and CAPOX followed by surgery) can be considered a new reference treatment in high-risk rectal cancer. Neo-adjuvant chemotherapy has been added as one treatment option in recent guidelines [124] and is used increasingly, especially to facilitate organ preservation after both conventional CRT and short-course RT [125][126][127][128][129].…”
Section: Neo-adjuvant Rather Than Adjuvant Therapy?mentioning
confidence: 99%